2016
DOI: 10.3892/or.2016.5224
|View full text |Cite
|
Sign up to set email alerts
|

Galangin suppresses human osteosarcoma cells: An exploration of its underlying mechanism

Abstract: Osteosarcoma is the most common malignant bone tumor that frequently affects adolescents. Osteosarcoma cells tend to proliferate and invade other tissues such as those of the lungs. Currently, neoadjuvant chemotherapy is the primary strategy to prevent tumor progression. However, its adverse effects result in poor long-term outcomes. Previous research has shown that galangin exhibits antitumor properties on several types of cancer cells; however its effect on osteosarcoma cells is yet unknown. The aims of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…In vivo experiments have also demonstrated the ability of quercetin to inhibit and prevent carcinogen-induced tumors in animals. Galangin was 20.8 mg/kg in jujube honey, which was reported in previous studied that it can induce autophagy through the upregulation of p53 in HepG2 cells (Wen, Wu, Luo, & Zhang, 2012), and the mechanism by which galangin suppresses human osteosarcoma cells has been elucidated (Yang et al, 2017). Although few studies have reported the anticancer effects of p-hydroxybenzoic acid, some fruits extracts enriched in p-hydroxybenzoic acid stimulate the apoptosis of human cancer cells in vitro (Seeram et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…In vivo experiments have also demonstrated the ability of quercetin to inhibit and prevent carcinogen-induced tumors in animals. Galangin was 20.8 mg/kg in jujube honey, which was reported in previous studied that it can induce autophagy through the upregulation of p53 in HepG2 cells (Wen, Wu, Luo, & Zhang, 2012), and the mechanism by which galangin suppresses human osteosarcoma cells has been elucidated (Yang et al, 2017). Although few studies have reported the anticancer effects of p-hydroxybenzoic acid, some fruits extracts enriched in p-hydroxybenzoic acid stimulate the apoptosis of human cancer cells in vitro (Seeram et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Another study has also revealed that galangin induces p53-mediated cell cycle arrest and the apoptotic process of nasopharyngeal carcinoma cells by suppressing the PI3K/Akt signaling pathway [53]. More recently, treatment of MG63 cells with galangin significantly inhibited the expression of cyclin D1 and MMP-2/9 via the suppression of PI3K and Akt phosphorylation [54]. In this study, we confirmed that these Akt/mTOR-dependent pathways play crucial roles in galangin reducing the MMP-9 expression induced by thrombin in SK-N-SH cells.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma, as one aggressive malignant, is prevalent in children and adolescents [1]. There are various treatment methods for osteosarcoma, such as preoperative chemotherapy, wide surgical excision, careful pathologic mapping of the resected tumor, and postoperative chemotherapy based upon the percentage of necrosis of the tumor [2,3]. Sadly, patients with high-grade osteosarcoma is characterized by metastasis normally have poor prognosis and outcomes [4].…”
Section: Introductionmentioning
confidence: 99%